2012
DOI: 10.1063/1.4753808
|View full text |Cite
|
Sign up to set email alerts
|

Record-low propagation losses of 154 dB/cm for substrate-type W1 photonic crystal waveguides by means of hole shape engineering

Abstract: Large propagation losses in the order 600-1000 dB/cm were reported in the past for planar line-defect photonic crystal waveguides with a weak vertical refractive index contrast (substrate-type). Loss-relevant factors are a well-suited design of the photonic crystal pattern and a high-quality fabrication technology. Here, the focus is on the latter. Two methods—a thermally driven mass transport process and an ultra-slow, selective wet-etching process—are assessed with respect to their capability of enabling low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A photonic crystal slab based on Si 3 N 4 has been demonstrated to work in the visible region of the electromagnetic spectrum. Moreover, photonic crystals based on InP/InGaAsP structure have been prepared with a slight loss [ 115 ].…”
Section: Waveguides and Applicationsmentioning
confidence: 99%
“…A photonic crystal slab based on Si 3 N 4 has been demonstrated to work in the visible region of the electromagnetic spectrum. Moreover, photonic crystals based on InP/InGaAsP structure have been prepared with a slight loss [ 115 ].…”
Section: Waveguides and Applicationsmentioning
confidence: 99%
“…Recent progress [6] showed that the angled-sidewall of the conical/cylindro-conical hole shape is responsible for the large propagation losses in these singlemode PhC waveguides. The hole shape can be improved by either etching deeper holes using a 800 nm-thick SiN x hard mask [7] or by hole shape engineering [8], which results in propagation losses as low as 150 -350 dB/cm. Both the thick SiN x hard mask and the hole shape engineering processes require additional processing steps.…”
mentioning
confidence: 99%
“…Attempts of realizing PhC travelling wave semiconductor optical amplifiers (SOAs) [4] are confronted by various challenges, e.g. excessive propagation losses due to mode leakage into substrate [5] as well as heating issues. However, recent progress within PhC Lasers [6,7,8] witness the continued development of the PhC membrane platform, indicating the feasibility of realizing PhC amplifiers.…”
Section: Introductionmentioning
confidence: 99%